Optimizing Chemical Tanker Performance: The Role of Cargo Control Operations and Crew Discipline - David Pandapotan Sirait; Esterlinus Edwin Lermatan; Marthaleina Ruminda (Siber Journal of Transportation and Logistics, 2026)
This study analyzes the impact of cargo control operations during Caustic Soda (CCS) loading/unloading and crew discipline on Motor Tanker operational performance at a South Korean shipping company. A quantitative survey approach was utilized, involving 35 crew members directly responsible for cargo handling. Data were analyzed through multiple linear regression and hypothesis testing via SPSS. Cargo control operations and crew discipline partially and simultaneously exert a positive, significant effect on operational performance, explaining 86.5% of the variance. Optimizing cargo control technology and enforcing strict crew discipline are crucial synergies for ensuring the smooth, safe, and efficient operation of vessels transporting hazardous chemical cargoes. The small sample size and specific focus on CCS cargo within one company may restrict the generalizability of these findings to other vessel types or cargo scales. This research provides strategic insights into maritime operational management, contributing empirical evidence on high-risk handling procedures for hazardous liquid chemicals.